From Self‐Assembly Hierarchical h‐BN Patterns to Centimeter‐Scale Uniform Monolayer h‐BN Film. Issue 1 (28th December 2018) - Geng, Dechao; Zhao, Xiaoxu; Zhou, Ke; Fu, Wei; Xu, Zhiping; Pennycook, Stephen J.; Ang, Lay Kee; Yang, Hui Ying
Abstract: The self‐assembly into highly ordered pattern is a universal phenomenon with unprecedented natural properties. However, the nonequilibrium processes in complex systems demand rigorous molecular formation mechanism, which are highly important for fundamental research. Herein, a large‐scale formation of highly self‐assembly hierarchical hexagonal boron nitride (h‐BN) superordered structures on a liquid Cu surface by the chemical vapor deposition (CVD) method is demonstrated. The hierarchical h‐BN superordered structure is found to be composed of two vertical stacking parts: one part is underneath h‐BN film and the other part is top orientated branched h‐BN patterns. In addition, the size, orientation, and morphology of the h‐BN superordered structures can be precisely tuned by varying the gas flow rate and growth time. A kinetics‐limited growth mechanism is proposed to elucidate the formation process, owing a well consistency with experimental results. Further, by mechanically peeling off the top few‐layer h‐BN, centimeter‐scale uniform monolayer h‐BN film is produced, demonstrating a direct and facile top‐down fabrication method. This synthesis of highly ordered hierarchical h‐BN patterns and following uniform monolayer h‐BN film can be applied to other 2D materials, paving way for great potential in the investigation of growth mechanism and construction of homo‐ and heterostructures. Abstract : A large‐scale formation of highly self‐assembly hierarchical hexagonal boron nitride (h‐BN) superordered structures on a liquid Cu surface by the chemical vapor deposition (CVD) method is demonstrated. This synthesis of highly ordered hierarchical h‐BN patterns and following uniform monolayer h‐BN film paves the way for great potential in the investigation of growth mechanism and construction of homo‐ and heterostructures.